Considerations on the status of the knowledge of coleopteran diversity (Arthropoda: Insecta) in Colombia - Girón, Jennifer C.; Amat García, Germán; Botero, Juan Pablo; Cardona-Duque, Juliana; Clavijo-Bustos, Julián; Díaz-Durán, Camila; García Concha, Jorge Humberto; García, Kimberly; López Murcia, Wilber; Lugo de la Hortúa, Andrés; Neita Moreno, Jhon Cesar; Ramírez-Salamanca, José M.; et al. (Revista Colombiana de Entomología, 2021)
Coleoptera is one of the most diverse orders on the planet, and Colombia one of the most biodiverse countries. The combination of these two factors determines with no discussion a high concentration of species, with only partially known consequences in the country. In this work we describe the current state of knowledge about the diversity of coleopterans in Colombia, highlighting the role of entomological collections and the knowledge gaps to tackle the national beetle fauna. This contribution is a starting point for coleopterologists of Colombia to begin working together towards a broader and less fragmented knowledge of the natural history, systematics, ecology, and biogeography of the group.